2010
DOI: 10.1371/journal.pone.0013568
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Soluble Junctional Adhesion Molecule-A as a Biomarker of Human Brain Endothelial Barrier Breakdown

Abstract: BackgroundAn inducible release of soluble junctional adhesion molecule-A (sJAM-A) under pro-inflammatory conditions was described in cultured non-CNS endothelial cells (EC) and increased sJAM-A serum levels were found to indicate inflammation in non-CNS vascular beds. Here we studied the regulation of JAM-A expression in cultured brain EC and evaluated sJAM-A as a serum biomarker of blood-brain barrier (BBB) function.Methodology/Principal FindingsAs previously reported in non-CNS EC types, pro-inflammatory sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 42 publications
1
34
0
Order By: Relevance
“…JAM-1 is believed to mediate early attachment of adjacent endothelial cells during BBB development through homophilic interactions and loss of JAMs is associated with BBB breakdown (19-22). For example, studies in an immortalized human brain endothelial cell line (hCMEC/d3) showed that inflammatory stimuli triggered movement of JAM away from the TJ, an observation that directly correlated with increased dextran leak across the BBB (23). Of particular note, JAMs are also implicated in the regulation of transendothelial migration of leukocytes (20, 24).…”
Section: Components Of the Nvumentioning
confidence: 99%
“…JAM-1 is believed to mediate early attachment of adjacent endothelial cells during BBB development through homophilic interactions and loss of JAMs is associated with BBB breakdown (19-22). For example, studies in an immortalized human brain endothelial cell line (hCMEC/d3) showed that inflammatory stimuli triggered movement of JAM away from the TJ, an observation that directly correlated with increased dextran leak across the BBB (23). Of particular note, JAMs are also implicated in the regulation of transendothelial migration of leukocytes (20, 24).…”
Section: Components Of the Nvumentioning
confidence: 99%
“…One was a human brain microvascular endothelial cell line which was established as a model for the blood brain barrier (BBB) [13][14][15]. These cells are stitched together by tight junctions that are composed of several transmembrane proteins forming a complex BBB [16][17][18].…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, loss of JAM protein expression is directly correlated with BBB disruption and injury (Yeung et al 2008; Hoffman et al 2009; Wang et al 2014). Additionally, studies in an immortalized human brain endothelial cell line (hCMEC/d3) showed that inflammatory stimulation led to increased paracellular solute diffusion, which correlated with JAM movement away from the tight junction, further suggesting a central role in maintaining BBB integrity (Haarmann et al 2010). …”
Section: The Blood-brain Barriermentioning
confidence: 99%